REDUCING DEFORESTATION THROUGH OPTIMIZATION OF NON-TIMBER FOREST PRODUCTS: A SOLUTIONAL APPROACH TO ACHIEVE CARBON EMISSION REDUCTION TARGET - Lydia Riekie Parera; Jusmy D. Putuhena; Renny Purnawati; Zeth Parinding (RADJA PUBLIKA, 2026)
Deforestation remains a critical environmental issue, contributing to biodiversity loss and increased carbon emissions, particularly in tropical forests. This study aims to explore how the optimization of Non-Timber Forest Products (NTFPs) can reduce deforestation and support carbon emission mitigation targets. Using a library-based research method, data were collected from primary and secondary sources, including books, scientific journals, reports, and case studies related to NTFPs, deforestation reduction, and carbon management. Content analysis was employed to identify patterns, relationships, and insights across the literature. Findings indicate that sustainable NTFP utilization provides alternative livelihoods, encourages community participation in forest management, preserves forest cover, and maintains carbon stocks. NTFPs demonstrate the potential to harmonize ecological conservation with socio-economic development, provided that supportive policies, governance frameworks, and monitoring mechanisms are implemented. The study concludes that integrating NTFPs into forest management strategies offers a practical, scalable solution for achieving both deforestation reduction and carbon emission mitigation objectives.